PENERAPAN PENYUSUNAN LAPORAN KEUANGAN UMKM BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) PADA USAHA KERIPIK 3 BINTANG - Aprilia, Imelda; Damanik, Destari Nurlaila; Panggabean, Fitri Yani (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research is titled “The Application of Financial Statement Preparation for MSMEs Based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in the 3 Bintang Chips Business.” The objectives of this research are (1) to analyze the financial information prepared by the 3 Bintang Chips MSMEs located on Jalan Yus Sudarso, and (2) to apply SAK EMKM in presenting the financial information for this MSMEs. This research uses a qualitative descriptive method with data collection techniques including literature review, interviews, observations, and documentation. The data used consists of both primary and secondary data. The research results indicate that: (1) The 3 Bintang Chips MSMEs has not yet prepared financial statements according to SAK EMKM because the business owner lacks understanding of the standards, and (2) there are several obstacles in implementing SAK EMKM, including: a. The owner and employees of the 3 Bintang Chips MSMEs have only a primary school education and no accounting background. b. The business believes that presenting financial information based on SAK EMKM is not beneficial for their operations. c. There is a lack of knowledge about SAK EMKM. d. There is no staff member who understands how to prepare financial statements according to SAK EMKM. There has been no outreach from relevant institutions to explain the importance of implementing SAK EMKM, so the business owners do not yet understand this.